AUDITORIA DE GESTIÓN AL TALENTO HUMANO DEL COLEGIO EXPERIMENTAL PIO JARAMILLO ALVARADO DE LA CIUDAD DE LOJA PERIODO 01 DE ENERO AL 31 DE DICIEMBRE DEL 2014 - Cueva Yaguana, Jimena Elizabeth (2016)
The thesis entitled "AUDIT OF HUMAN TALENT MANAGEMENT COLLEGE OF EXPERIMENTAL PIO JARAMILLO ALVARADO the city Loja PERIOD 01 JANUARY TO 31 DECEMBER 2014" was held to meet a requirement of the National University of Loja, prior to choose the Bachelor of Engineering in Accounting and Auditing, Certified Public Accountant - Auditor and for compliance with the following specific objectives were set. The first specific objective is to "evaluate the internal control system of the Department of Human Talent Pio Jaramillo Alvarado Experimental College to determine the efficiency and effectiveness", which was developed through the application of SWOT to know the strengths, weaknesses, opportunities and threats in each of the areas of this institution and then be evaluated by the internal control questionnaire in management, administrative and educational components to safeguard assets, promote efficiency, minimize errors and ensure the reasonableness of general. The second objective is "To verify compliance with laws and regulations in their particular functions of the Department of Human Resource" public sector institutions especially the experimental school must comply with rules, laws, statutes and regulations of the institution, which They were analyzed to verify their compliance with the directive, administrative and teaching part. The third specific objective is, "she Apply management indicators for determining the efficiency and effectiveness for meeting the objectives and goals of the institution," he was executed based on the application of indicators of efficiency and effectiveness, the Executive, Administrative and Teachers components arriving determine the rational use of available resources at minimal cost and achieving the goals set. 6 The fourth specific objective is to "prepare the report Auditing the Experimental College Pio Jaramillo Alvarado containing conclusions and recommendations for improvement of the institution", recorded at the end of the audit report led managers to take corrective measures allowed to improve management and in this way contribute to the development of this prestigious educational institution. The methodology used was to gather the information needed for the development work which began with planning, establishing an initial diagnosis, then the execution in which tests and procedures applied, was based on the analysis of clear questions asked in the questionnaire internal control, the narratives of the findings was performed, management indicators was applied to measure the efficiency and effectiveness, concluding with the audit report containing conclusions and recommendations. Upon completion of the thesis by assessing the internal control system, it was determined that have not performed any audit management that allows you to know exactly the degree of efficiency and effectiveness, and have fulfilled the activities and functions within the